Aktualisasi Nilai-Nilai Pendidikan Agama Islam dalam Pembentukan Karakter dan Akhlak Mulia : Telaah Pemikiran Imam Al-Ghazali dalam Kitab Ihya' Ulumuddin - Huan Akmal Hasibuan; Selamat Pohan (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
Islamic Religious Education plays an important role in shaping students’ character and noble morals amid the various challenges of modern life. The current moral crisis indicates that education has not fully succeeded in developing individuals with commendable character. Therefore, it is necessary to strengthen Islamic educational values that are oriented toward character formation. One of the prominent scholars who paid significant attention to moral education was Imam Al-Ghazali through his monumental work, Ihya' Ulumuddin. This study aims to analyze the actualization of Islamic Religious Education values in character building and the development of noble morals based on Imam Al-Ghazali's educational thought. The research employs a qualitative approach using a library research method. Data were collected from the Ihya' Ulumuddin, books, scholarly journals, and other relevant literature. The findings reveal that, according to Al-Ghazali, the values of Islamic education include faith (iman), worship (ibadah), morality (akhlaq), self-discipline through spiritual struggle (mujahadah al-nafs), exemplary conduct (uswah hasanah), and habituation of good deeds. These values are highly relevant in fostering religious character, honesty, discipline, responsibility, social concern, and integrity among students in the modern era. Al-Ghazali's educational thought remains relevant for application in contemporary education as a solution to the moral degradation occurring in society.